2014
DOI: 10.1055/s-0038-1626198
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive carpal tunnel surgery in leprosy

Abstract: PALAVRAS-CHAVESíndrome do túnel carpal, hanseníase, nervo mediano.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 9 publications
1
5
0
4
Order By: Relevance
“…Another factor that contributed to most patients considering the surgery satisfactory was the reduction in pain intensity. In the individuals evaluated, a sharp drop in pain intensity was found when the PrO pain was compared to LPO pain, similar to results of other studies 3,[12][13][14] . However, a considerable proportion of patients presented neuropathic pain during the LPO period, reinforcing the need to optimize pain treatment in these patients, including differentiating between chronic pain and new reaction episodes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Another factor that contributed to most patients considering the surgery satisfactory was the reduction in pain intensity. In the individuals evaluated, a sharp drop in pain intensity was found when the PrO pain was compared to LPO pain, similar to results of other studies 3,[12][13][14] . However, a considerable proportion of patients presented neuropathic pain during the LPO period, reinforcing the need to optimize pain treatment in these patients, including differentiating between chronic pain and new reaction episodes.…”
Section: Discussionsupporting
confidence: 88%
“…However, after a Cochrane's review of the subject, it was concluded that the results of these studies were not sufficient to evaluate the effects of the surgery, and that new studies with larger populations and with long-term follow-ups were necessary to evaluate the possible favorable predictive factors for decompressive surgery 8,11 . The epidemiological and clinical profiles of these patients make them inappropriate for randomized controlled trials; in addition, non-randomized studies that evaluated the effects of PNSD showed a tendency toward pain relief 3,[12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Contrariamente, estudos observacionais, retrospectivos, demostraram que aqueles indivíduos submetidos ao procedimento cirúrgico apresentaram, principalmente, o alívio da dor, indicando ser tal conduta uma terapia complementar que mereça ter os seus resultados mais bem investigados (SAID et al, 1973: PALANDE;AZHAGURAJ, 1975;CHAISE et al, 1982;BRANDSMA et al 1983;BERNADIM;THOMAS, 1997;DEBRAY et al, 2001;JAMBEIRO, 2008;PONDÉ, 2010;PONDÉ, 2014…”
Section: Tratamento Cirúrgico Da Neuropatiaunclassified
“…O nervo ulnar é o mais frequentemente acometido na hanseníase (PIMENTEL et al, 2003;JAMBEIRO et al, 2008;REDONDO, 2009;REIS et al, 2013), por isso, houve maior número de cirurgias indicadas nos membros superiores nesse estudo. (SAID et al, 1973;PALANDE;AZHAGURAJ, 1975;CHAISE;BRANDSMA et al, 1983;BERNADIN;THOMAS, 1997;DEBRAY et al, 2001;HUSAIN;MALAVIYA, 2008;JAMBEIRO et al, 2008;PONDÉ, 2010;PONDÉ et al, 2014). Alguns autores chegaram a relatar que o principal benefício da cirurgia de descompressão neural é o alivio da dor, e que a recuperação sensitivo-motora pode ser um achado acidental (VAIDYANATHAN;VAIDYANATHAN, 1968;BOUCHER et al,1999 , 2000).…”
Section: 2 Sensibilidadeunclassified
See 1 more Smart Citation